Optimization Analysis of Hydro-static Sliding Bearing with Water Lubrication Spiral Step - Long Shenwen; Wang Youqiang; Zhou Yabo; Wei Cong (Jixie chuandong)
Based on ANSYS finite element static analysis,the mechanical properties of the water lubricated spiral stepped rubber stern bearings are obtained by orthogonal design and control variable method. Based on the results,the influence of structural parameters on the mechanical properties of the stern bearings is obtained based on Minitab. Finally,the surface structure of the stern bearings is analyzed by Design Exploration module and the multi-objective optimization is used to improve the mechanical property.